Los ejércitos coloniales y la crisis del imperio español, 1808-1810 - McFarlane, Anthony (El Colegio de México, A.C., 2008)
This article examines the character of the Spanish American military  and its responses to the crisis of the Spanish monarchy in 1808-1810, and argues that military men, especially officers, were  often  crucial  in sustaining  or  subverting  Spanish  rule  in the opening phase of the crisis. To understand the position of the military, it focuses on three main areas of analysis: first, the extent to which the character of Spanish armed forces in the colonies was altered by Bourbon military  reforms;  second,  the reaction of the  reformed  colonial  forces  to  the  crisis of the  monarchy; third,  the extent of variation, and the reasons for differences, in military responses in the major cities of Spanish America.